"Taonga pūoro is more for the wairua and less for your ears" : Māori perspectives and experiences of taonga pūoro and its potential as rongoā : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Te Kunenga ki Pūrehuroa, Manawatū, Aotearoa New Zealand - Cashell, Abigail Kahurangi (Massey University, 2021)
Taonga pūoro (Māori singing treasures) historically held many functions in everyday Māori life. Colonisation had catastrophic consequences for these taonga (treasures), yet they have seen a continued renaissance for the past 40 years. A growing body of mātauranga (knowledge) exists in contemporary contexts suggesting taonga pūoro can provide a uniquely Māori approach to enhancing healing, hauora (a Māori philosophy of health), and wellbeing. The aim of this Kaupapa Māori rangahau (research) was to explore Māori perspectives and experiences of taonga pūoro and its potential as rongoā (Māori healing). 14 Māori participants contributed their whakaaro (thoughts) through semi-structured interviews and their kōrero (discourse) was analysed using a reflexive approach to thematic analysis. The findings show Māori use the explanatory framework of whakapapa (genealogical principle) to understand taonga pūoro. With this interconnected understanding they had profound healing experiences that were considered cathartic through the release of multilayered mamae (pain). Most significantly, the healing influenced participants wairua (spirit), the foundational aspect of Māori hauora that may be difficult to attend to in non-Māori healing modalities. Continued processes of colonisation present barriers to taonga pūoro being used as rongoā. However, taonga pūoro was proposed to ultimately heal and overcome these challenges through reconnection to multiple layers of te ao Māori (the Māori world). This research contributes important mātauranga for Māori and mental health practitioners about the therapeutic value taonga pūoro may hold. Māori experienced significant hauora benefits from taonga pūoro in multiple domains, something that is pertinent at this point in history when Māori are experiencing heighted levels of psychological and social distress. This rangahau supports further exploration of the healing practices of tūpuna Māori (Māori ancestors) to assist in overcoming modern hauora challenges.
Keywords: Māori Masters Thesis; 451014 Ngā pūnaha mātauranga hinengaro o te Māori (Māori psychology knowledge systems)